Practical guide to software quality management - Horch, John W. (Artech House computing library., 2003)
If you are responsible for designing, implementing, or managing a quality software program, this updated edition of the Practical Guide to Software Quality Management now identifies 10 major components that make up a solid program in line with ISO 9001 quality management precepts. Thoroughly revised and with new chapters on software safety and software risk management, this comprehensive primer provides you with the starting points for a standardized documentation system, and analyzes each individual program component separately, addressing in detail its specific role and overall importance to the system. This is the only volume to offer a broad overview of software quality management for non-experts and experts alike. It is written in clear, easy-to-understand language and contains a complete glossary that demystifies technical terms, abbreviations, and acronyms. Useful appendices contain example and "starting point" documentation outlines. Moreover, every chapter features an extensive list of authoritative references directing you to the latest technical details on a variety of software quality management issues.